Structural adjustment and the changing face of education. - CARNOY, Martin (1995)
Explains the nature of the main types of reforms in the education sector which have resulted from structural adjustment policies. Discusses the impact of these reforms on the quality of education and considers the possibility of alternative policies for adjustment.